Implementation of new technologies into the educational process to improve efficiency - Vzhytynska (Omelchenko), Kseniia (My University, 2015)
The information of a modern society is actively reflected in educational process. Currently it is not possible to imagine educational process without the introduction and implementation of new educational technologies in it.
Keywords: educational technology; new technology; educational process; освітні технології; освітній процес; нові технології; образовательный процесс; новые технологии; образовательные технологии; кафедра економічної теорії